A framework for remotely enabled co-design with young people: its development and application with neurodiverse children and their caregivers - Morris, Anna Charlotte; Douch, Stephen; Popnikolova, Teodora; McGinley, Chris; Matcham, Faith; Sonuga-Barke, Edmund; Downs, Johnny (Frontiers in Psychiatry, 2024)
Introduction -This paper describes an innovative Framework for Remotely Enabled Co-Design with Young people (FREDY), which details an adaptable four-stage process for generating design concepts with children and other key stakeholders in a naturalistic and inclusive way.Methods -Recommendations from existing patient engagement and design methodologies were combined to provide research teams with procedures to capture and analyse end-user requirements rapidly. Resulting insights were applied through iterative design cycles to achieve accelerated and user-driven innovation.Results -Applying this framework with neurodiverse children within the context of healthcare, shows how creative design methods can give rise to new opportunities for co-creating across diverse geographies, abilities, and backgrounds as well as strengthen co-designecreator approval of the codesign process and resulting product.Discussion -We summarise key learnings and principles for fostering trust and sustaining participation with remote activities, and facilitating stakeholder design input through continuous collaboration, as well as highlight the potential benefits and challenges of utilising FREDY with neurotypical populations.